(untitled) (UUM Journal of Legal Studies, 2024)
This paper aims to evaluate the peculiarities of a mechanism utilised by the Indonesian government to conduct infrastructure development, that is, the government’s assignment of contracts to state-owned enterprises (SOEs). This mechanism differs from public procurement or public-private partnership. This paper raises three questions: (1) What are the advantages and disadvantages of employing government assignment of contracts to SOEs? (2) What should be done to prevent the disadvantages? and (3) What lessons can be learned by other countries from the Indonesian experience? This paper employs qualitative legal research. It starts by analysing public satisfaction and dissatisfaction as reflected in the news, literature and interviews. The legal causes of dissatisfaction which are basically the problematic regulations, are then analysed. Finally, the legal principles and legal concepts enshrined within the regulations are examined to seek legal solutions. The advantages of the government’s assignment of contracts to SOEs are to simplify the tender process and to enable the government to quickly provide infrastructure. Nonetheless, the private sector feels aggrieved because the regulations that dictate when a project may be contracted to an SOE are unclear, and public funding is predominantly circulated among the SOE groups. To address these problems, the government should adhere to the globally recognised principles of equality and accountability and the concepts of competitive neutrality and the right to development. The bittersweet Indonesian experiences maybe not only the refinement of the Indonesian law and policy, but also their use as food for thought for any country considering infrastructure development.